BRILink: Impact on Economic Welfare During the Covid-19 Pandemic in Praya Barat - Selamat Muliadi (Innovation Business Management and Accounting Journal, 2022)
BRI provides financial services through BRILink agent at remote villages. BRILink agent give service not only provides operational efficiency benefits, but also provides convenience for BRI’s customers and non customers. Phenomena that often occur in BRI Bank customers against Brilink Agents, both directly and indirectly, such as the quality of service provided to customers that are not up to standard so that it can lead to the customer's decision to return to transactions at Brilink Agents and the impact of these problems will decrease the number of transactions and decreased fee-based income for Brilink agents. This study aims to test and analyze the effect of BRILink on economic welfare in Praya Barat Central Lombok Regency during the Covid-19 Pandemic. The research used the quantitative method with case study approach. The method that used multiple linear regression with the numeric variable include Classic Assumption Test. The data source was primary data and collection techniques conducted by interviews and observation. Respondents in this study we 27 agents of the BRILink in Praya Barat. The results showed that the number of agents and the number of transactions has a significant and positive effect on economics welfare in Praya Barat.